Capacity Building in Fundraising and Organizational Digitalization of LAZISMU Turkey Based on Muhammadiyah Values - Muzakar Isa; Praswati, Aflit Nuryulia; Rahmatdi; Ahmada Auliya Rahman; Nurul Latifatul Inayati; Alfina Rahmatia (Universitas Muhammadiyah Surakarta, 2025)
In the era of globalization and digitalization, philanthropic organizations are required to be adaptive in managing donations, strengthening ideological values, and developing sustainable institutional capacity. This community service proposal aims to strengthen the institutional capacity and philanthropic governance of LAZISMU Turkey through a series of integrated programs. The main activities include: (1) a Global Fundraising & Digital Marketing Workshop conducted in a blended format to develop fundraising strategies that reach Turkish and international donors, with the target of launching two digital campaigns; (2) strengthening AIK (Al-Islam and Muhammadiyah Values) and the Muhammadiyah philanthropic ethos through online activities and cadre development discussions to enhance understanding of AIK and to establish an internal cadreization team; (3) the development of a professional LAZISMU Turkey website through redesign, optimization of donation features, and technical training so that the website functions as a primary communication and donation channel; and (4) the formulation of an organizational development and cadreization roadmap using a participatory approach through focus group discussions (FGDs) and mentoring, resulting in a three-year roadmap for institutional strengthening.